Estudio de factibilidad de un centrode cultura y desarrollo del arteconn atención para las personas con discapacidad física cantón el Empalme, año 2014 - Vinces Parra, Lita Elvira (2015)
The work of thesis presented aims to determine the feasibility of the Centre of culture and art development with care for people with physical disabilities in the Canton the joint year 2014. Today being applied art as occupational therapy for people with disabilities, this is why it is very important to focus on these activities through art can strengthen their skills and abilities, this directly benefits in the social development of persons with disabilities. The objective aims to through the application of art promoting the rehabilitation and integration of people with disabilities in society, is important to have the necessary resources for its implementation. Educate the community on the subject of disability through spaces of coexistence between people with and without disability through artistic expression. Promote respect, tolerance and empathy to the diversity of people, thus contributing to a culture of inclusion real, recognizing the opportunity for artistic enrichment and the subject of disability awareness….